Effectiveness of Controlled MDM2 Inhibitor Release on Brain Tumor Cells in vitro - Zengin, Elifcan; Calis, Seyma; Avsar, Timucin; Onder, Sakip (IEEE, 2019)
Cancer is a significant health issue all over the world causing severe decline in life expectancy of patients and their life standards. Traditional cancer treatment methods such as chemotherapy, surgical intervention and radiotherapy lead to critical side effects such as systemic toxicity and drug resistance development. In the last decades, controlled drug delivery systems have been studied to overcome those limitations. The study aims controlled drug release treatment on brain cancer cells. Therefore, chitosan microspheres were potentially used as drug carriers, and MDM2 inhibitory molecule was selected as a model drug to assess the cell viability of T98G brain tumor cell line. MDM2 inhibitor-loaded chitosan microspheres were produced by the emulsion/cross-linking method. MDM2 inhibitory molecule release profile in vitro was carried out in phosphate-buffered saline at pH 7.4. Moreover, effects of drug-loaded microspheres on brain tumor cells were tested by MTT assay.
Keywords: chitosan microspheres; controlled drug delivery; MDM2 inhibitor; Engineering